Survival in hostile territory: the microbiota of the stomach. Issue 5 (22nd July 2013) - Yang, Ines; Nell, Sandra; Suerbaum, Sebastian
Abstract The human stomach is a formidable barrier to orally ingested microorganisms and was long thought to be sterile. The discovery of Helicobacter pylori, a carcinogenic bacterial pathogen that infects the stomach mucosa of more than one half of all humans globally, has started a major paradigm shift in our understanding of the stomach as an ecological niche for bacteria. The special adaptations that enable H. pylori to colonize this well‐protected habitat have been intensively studied over the last three decades. In contrast, our knowledge concerning bacteria other than H. pylori in the human stomach is still quite limited. However, a substantial body of evidence documents convincingly that bacteria can regularly be sampled from the stomachs of healthy adults. Commonly detected phyla include Firmicutes, Actinobacteria, Bacteroidetes, and Proteobacteria, and characteristic genera are Lactobacillus, Streptococcus, and Propionibacterium. In this review, we summarize the available literature about the gastric microbiota in humans and selected model animals, discuss the methods used in its characterization, and identify gaps in our knowledge that need to be addressed to advance our understanding of the bacterial colonization of the different layers of the gastric mucosa and its potential role in health and disease.